Problems in Coordinating International Cooperation to Combat Transnational Organized Crime - Boubaia, Kamel; Ouali, Abdellatif (Journal of Legal Studies and Researches, 2021)
Transnational organized crime has become the subject of widespread debate in international forums, given its serious implications, both at the political, political, economic and security levels, which has created a conviction among the international community of the need to tackle and combat this crime. International and regional organizations and institutions have adopted a wide range of international protocols and conventions, the most important of which is the United Nations Convention against Transnational Organized Crime in 2000.However, this legal arsenal has not borne the desired fruit for different reasons.